Study on National Standard School Examination and School Examination in Elementary Schools - Fatimatus Zahrah; Toho Cholik; Yoyok Soesatyo; Dedi Irawandi (AIBPM Publisher, 2023)
This research is descriptive qualitative research, namely a data presentation in the form of a brief, concise but clear, and easy-to-understand description. This research aims to describe and analyze the National Standardized School Exams and School Exams in elementary schools as standard assessment tools for school exams in Elementary Schools (Multi Case Study at Lawangan Daya 2 Public Elementary School and Al-Munawwaraah Islamic Elementary School, Pamekasan Regency). The data collection procedure is the interview method, with in-depth interview techniques, observation or observation, and documentation studies. The data analysis technique used uses single case data analysis with the Miles and Huberman model, namely data condensation, data display/presentation, verification and drawing conclusions. The results of the study show that the implementation of national standard school exams will encourage schools to prepare students before the exam is held.